Handedness helps homing in swimming and flying animals - Bandyopadhyay, Promode R. (Nature Publishing Group, 2013)
Swimming and flying animals rely on their ability to home on mobile targets. In some fish, physiological handedness and homing correlate, and dolphins exhibit handedness in their listening response. Here, we explore theoretically whether the actuators, sensors, and controllers in these animals follow similar laws of self-regulation, and how handedness affects homing. We find that the acoustic sensor (combined hydrophone-accelerometer) response maps are similar to fin force maps—modeled by Stuart-Landau oscillators—allowing localization by transitional vortex-propelled animals. The planar trajectories of bats in a room filled with obstacles are approximately reproduced by the states of a pair of strong and weak olivo-cerebellar oscillators. The stereoscopy of handedness reduces ambiguity near a mobile target, resulting in accelerated homing compared to even-handedness. Our results demonstrate how vortex-propelled animals may be localizing each other and circumventing obstacles in changing environments. Handedness could be useful in time-critical robot-assisted rescues in hazardous environments.